A constituição e representação de identidades femininas no discurso publicitário - Pivetta, Graziela Thais Baggio (2009)
This thesis focuses its discussion on the relationship among the advertising discourse and the processes of formation and representation of woman-subject s. We started the journey with the resumption of the theoretical frame of reference, the review of French Speech, under the approach of Michel Pêcheux, that not thought untied the language of history, ideology, and games of Power. In the theory of discourse, we found the safe harbor , in that we could dock, and thus we established clippings in the file that was in our corpus, launching a look that focus not only the linguistic aspect, but that reflected on the fact that all non-verbal materiality produces meaning(s), among with the production conditions, enrolling, then, itself, in the order of speech. The main objective is to put under suspicion, say so, the direction(s) that are offered in advertisements and naturals and fixed, bringing/proposing questions about this naturality of senses, which, supposedly, can only mean in that way. The procedure of analysis focuses on the effects of ideological operation in/for the construction of female identity that considers the diversity of roles of the women in current society and, in the same time, that recognizes unstopped exaltation and worship to the body and its (good) physical form and aesthetics as mechanisms related to seduction and Power. Finally, we observed that the mechanisms of formation of these senses that prime for uniformity of women-subject pass through her body, because it is through and through the Power called by its extreme value, that the imaginary organizes senses in our social reality by introducing them as truth and incorporating them into the provisional address of a fragmented identity that, necessary and illusory, it is understood/seen as unified and resolved so that we can (re)produce the same senses